A plant starch/ oil extracting machine. - Mustapa Kamal, Siti Mazlina; Mahmud, Siti Norfadhillah (2009)

(untitled)
This invention relates to an equipment and squeezing desired substance from fruits and tuber plants (such as tapioca, sweet potato and jatropha) in the form of liquid (such as starch and oil), as well as crunching and rupturing the pith of the palm trunks such as sago palm for the purpose of starch extraction. It is suitable for use in small and medium-scaled industrial operation. This portable machine is secured with a steel housing as a safety feature, easy to operate and user-friendly. It consists of a feeder through which the feed is inserted and consume spin the feed, while the square blades cut, compress and crush the feed into fine bits. The crushed feed falls through to the bottom container and is conveyed into the pressing section where a screw press squeezes it to extract starch or oil. A steel barrel with linear gaps running the length of its body houses the press and acts as a screen to allow only desired liquid to pass through. A slanted funnel resides below the pressing section to facilitate the flow of the extracted liquid from the barrel into a container. The pressed feed is moved along the screw press by steel coils and is discharged as residual waste through an opening at the end of the press. This invention crushes and presses feeds effectively, giving maximum yield and very minimal loss. The process is also reasonably hygienic, consumes minimal time and requires minimal supervision. Therefore, this invention leads to a more efficient operation with reduced operating costs.